Cariprazine augmentation of clozapine in schizophrenia-a retrospective chart review - Marcin Siwek; Adrian Andrzej Chrobak; Aleksandra Gorostowicz; Patrycja Król; Dominika Dudek (Frontiers Media S.A., 2024)
The aim of our study was to evaluate the efficacy of cariprazine augmentation of clozapine in treatment-resistant schizophrenia in a retrospective chart review. Among 916 medical records of schizophrenia patients, we identified 12 individuals treated with a combination of those drugs for a duration of 3-60 weeks [median 32 (10-40)]. Clinical Global Impression-Improvement (CGI-I) scores were used to measure the treatment response between the introduction of cariprazine augmentation of clozapine and the last point of observation. The majority of the patients presented treatment response (9/12 patients, 75%) after 4-16 weeks of therapy [median 6 (4-12)]. Treatment was associated with the decrease in positive, negative, affective, and anxiety symptom severity, as well as improvement of patient global functioning. One patient discontinued the treatment due to side effects (akathisia), and two patients halted the therapy due to the exacerbation of psychotic symptoms. Our study presents a thorough clinical description of the largest number of treatment-resistant schizophrenia patients medicated using cariprazine augmentation of clozapine in a "real-world" setting. Our results suggest that the use of this combination may lead to the improvement in a broad range of symptoms of patients with this condition.